Screening for alcohol and substance use for older people in geriatric hospital and community health settings. (23rd September 2014) - Draper, Brian; Ridley, Nicole; Johnco, Carly; Withall, Adrienne; Sim, Welkee; Freeman, Matilda; Contini, Erika; Lintzeris, Nicholas
ABSTRACT: Background: We aimed to determine the rates of alcohol and substance use in geriatric hospital and community health settings, and to evaluate the performance of screening instruments. Method: A two-phase cross-sectional study was undertaken in geriatric and aged care psychiatry wards and associated community services of a teaching hospital. Participants were screened with the Brief Alcohol Use Disorders Identification Test (AUDIT-C) and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) for other substances; Geriatric Depression Scale-15 for mood; the Connor–Davidson Resilience Scale; and the Subjective Quality of Life scale. Medical conditions were established. Screen positives for risky substance use continued with the full AUDIT, full ASSIST, CAGE, Addenbrooke's Cognitive Examination-Revised, and the Functional Activities Questionnaire. Medical records were reviewed after three months to ascertain recognition and management of substance use. Results: Of 210 participants aged 60+ (mean age 81.9, 63.3% female) without dementia or delirium and Mini Mental State Examination score ≥24, 41 (19.5%) were screen positive – 36 (17.1%) for alcohol, seven for non-medical benzodiazepine use (3.3%) (four alcohol and benzodiazepine) and two for non-medical opioid use (0.95%). Screen positives differed from screen negatives on few demographic or health measures. On the ASSIST, 26 (12.4%) were rated as medium/high risk. The AUDIT-C with cut-point of ≥5 was the optimal measure for detecting risky alcohol use. Conclusions: Many patients in geriatric health services have risky alcohol or substance use, but few clinical features distinguish them from other patients. Routine screening of alcohol and substance use is recommended.